PROBLEMS OF NONLINEAR EFFECTS AND DISEQUILIBRIUM IN MODERN WORLD POLITICS (Scientific journal of the Fergana State University, 2025)
In this article, the author examines nonlinear and non-equilibrium processes in world history and modern politics, analyzes the relationship between the properties of bifurcation and chaos, and the processes of self-organization using a synergetic method.